Photosensitivity, grating strength and thermal endurance of fibre bragg gratings / Dinusha Serandi Gunawardena - Dinusha Serandi, Gunawardena (2016)
Fibre Bragg gratings (FBGs) are wavelength selective fibre structures composed of periodic refractive index changes which occur in the fibre core due to high intensity UV irradiation. FBGs are considered to be the backbone of optical fibre technology. Thus, the main goal of this thesis is to conduct a comprehensive investigation on the photosensitivity, the grating strength and the thermal endurance of fibre Bragg gratings. This thesis elaborates on the photosensitivity and thermal properties of a new type of optical fibre known as gallosilicate fibre. Gallosilicate fibre provides enhanced photosensitivity compared to the widely used germanosilicate fibre when exposed to 193 nm ArF excimer laser at low UV fluence levels. In addition, these fibres consisting of a single dopant with a concentration as a low as 5 wt%, possess high temperature grating regeneration characteristics, thereby making them potential candidates for high temperature resistant gratings. One of the prime intentions of this thesis is to propose a mathematical model in order to explain the formation of the grating structure in photosensitive germanosilicate fibres by using a combination of KrF excimer laser and phase-mask. The growth characteristics of these two local refractive index changes are compared and represented by a single characteristic function. Since grating and interference visibilities are the two key parameters which influence the grating strength of an FBG, a new measurement technique is introduced to estimate the interference visibility. Another technique, which is based on the bent-spectral analysis method is also proposed for precise determination of the grating visibility of an FBG. The grating visibility is estimated with the aid of a simple mathematical expression by varying “ac” and “dc” coupling coefficients at different bending radii. The effect of the decreasing bending radius on the Bragg Transmission Depth (BTD), and both the “ac” and “dc” coupling coefficients are thoroughly explored. Moreover, the influence of the degradation of coupling coefficients on the centre wavelength shift is investigated. The accuracy of the model proposed is verified with experimental results. The main contribution of this thesis is the investigation of thermally induced reversible effect present in gratings inscribed in PS 1250/1500 fibre. The grating strength of a grating with prolonged thermal endurance is characterised over a time period of a thousand years over a temperature range of 200 °C to 400 °C. A noteworthy increment in the grating reflectivity is observed during annealing at 425 °C, deviating from the general thermal decay behaviour of an FBG. A comprehensive investigation is carried out on both stepwise and continuous annealing procedures which indicate a similar trend in the accelerated ageing characteristics when analysed with respect to the demarcation energy (Ed) domain. Finally, the salient features of alteration in the temperature ramping rates, on the grating strength is analysed in detail by performing thermal annealing procedures on three different types of Bragg gratings where a comparative exploration is carried out.